Faktor- Faktor yang Berhubungan dengan Penyakit Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Temindung Kota Samarinda - Desy Hajizah; Irfansyah Baharuddin Pakki; Ayudhia Rachmawati; Siswanto, Siswanto; Muh Amri Arfandi (Yayasan Literasi Sains Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern, particularly in tropical regions such as Indonesia, where it has persisted for over five decades. In 2023, Samarinda ranked third among ten regencies or cities in East Kalimantan with the highest number of DHF cases. One of the primary health centers consistently ranking among the top three with the highest DHF cases in Samarinda from 2021 to 2023 is Temindung Public Health Center. Environmental conditions and community behavior are believed to play significant roles in the transmission of this disease. This study aimed to identify factors associated with DHF incidence, including the condition of water storage containers (TPA), lighting, the presence of mosquito larvae, and Mosquito Nest Eradication (PSN) behavior. A cross-sectional design with a quantitative approach was used, involving 138 respondents selected through purposive sampling within the working area of Temindung Public Health Center. Data were collected using questionnaires, direct observation, and lighting measurements, and analyzed using the Chi-square test. The results showed significant associations between the availability of TPA covers (p = 0.037), household lighting (p = 0.017), PSN behavior (p = 0.000), and the presence of mosquito larvae (p = 0.000) with DHF incidence. These factors are interrelated in increasing the risk of DHF transmission in residential areas. Proper management of water storage, adequate household lighting, mosquito larvae control, and improved PSN behavior are crucial in reducing DHF cases. Active involvement of both the community and public health centers is essential in implementing continuous and sustainable preventive measures.